GOOD GOVERNANCE AND THE USE OF SOCIAL NETWORKS FOR AGRIBUSINESS IN NIGERIA (Isagoge - Journal of Humanities and Social Sciences, 2021)
The world population increases rapidly, and hence food supply, proportional to the need of the teeming population, remains a critical challenge confronting stakeholders. Thus, there is a need to develop strategies to boost agriculture, and this course must be planned, arranged, tested, evaluated, and implemented. In this context, good governance and the use of social networks are proven to make a tremendous contribution in boosting agricultural outputs. Nigeria was an agro-based nation until oil products were discovered in the middle of the 1950s. This discovery led to the country’s over-dependence on oil products, which negatively altered its level of food production. However, the current administration is determined to “diversify the country’s oil-denominated economy by investing more in agriculture and encouraging farming. Thus, this paper discusses how good governance and the use of social networks can help promote agribusiness in the Nigerian context. Discussion of this kind is crucial as good governance determines the success or failure of a given nation, and society depends, to a certain extent, on the media for information about various aspects of life, including agriculture. The outcomes of this study are expected to advance our knowledge and suggest further evidence-based research on good governance and the use of social media for agribusiness promotion.
Keywords: Agribusiness; Governance; Food security Nigeria; Social Networks